Obesity and Trends in Life Expectancy - Helen L. Walls; Kathryn Backholer; Joseph Proietto; John J. McNeil (Journal of Obesity)
Background. Increasing levels of obesity over recent decades have been expected to lead to an epidemic of diabetes and a subsequent reduction in life expectancy, but instead all-cause and cardiovascular-specific mortality rates have decreased steadily in most developed countries and life expectancy has increased. Methods. This paper suggests several factors that may be masking the effects of obesity on life expectancy. Results. It is possible that health and life expectancy gains could be even greater if it was not for the increasing prevalence of extreme obesity. It is also possible that the principal impact of obesity is on disability-free life expectancy rather than on life expectancy itself. Conclusion. If the principal impact of obesity were through disability-free life expectancy rather than on life expectancy itself, this would have substantial implications for the health of individuals and the future burden on the health care system.